Developer Confidence in Continuous Integration: Definition and Supporting Aspects - Aslam, Ayesha; Naganalli, Annapurna Ashok (My University, 2018)
Context Organizations are facing a lot of challenges, both social and technical, in adopting continuous practices. In the midst of these challenges, little is known about how software developers are dealing with the usage of continuous integration as its immediate users. Objective The objective of this study is to address the confidence related behaviour of developer in the context of continuous integration by proposing its definition and how it can be supported through features in CI tools and aspects in work environment. Method A case study is conducted in a IT consultant company where developer’s confidence is explored through interviews and workshop with developers having varied experience levels. Result Developer’s confidence depends on their knowledge and the quality of tests they add. Conditionally, it also depends on their confidence in CI tool and coworkers. Various features in CI tool and environmental aspects are identified that can potentially support developer’s confidence in the context of continuous integration. These findings can help organizations in overcoming adoption challenges to continuous integration by supporting developer’s confidence. Conclusion To conclude, developer’s confidence can be potentially supported to overcome adoption challenges in CI. Our findings for features in CI tools and environmental aspects can be implemented in organizations to validate their effectiveness and can serve as an inspiration to support developers for successful adoption of CI.
Keywords: Data- och informationsvetenskap; Computer and Information Science